2007
DOI: 10.1007/s11095-007-9496-9
|View full text |Cite
|
Sign up to set email alerts
|

HNF4α is a Crucial Modulator of the Cholesterol-Dependent Regulation of NPC1L1

Abstract: It is concluded that HNF4alpha plays a crucial role in the expression and regulation of human NPC1L1 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 28 publications
2
42
2
1
Order By: Relevance
“…Regarding the regulatory mechanism of NPC1L1 expression, we demonstrated that, in addition to SREBP2, several transcriptional factors such as hepatocyte nuclear factor 4α (HNF4α/NR2A1), peroxisome proliferator-activated receptor α (PPARα/NR1C1), and PPARγ coactivator 1α (PGC1α) positively regulate the mRNA expression of NPC1L1. 15,49) Taken together with facts that both HNF4α and PPARα are involved in the pathogenesis of diabetes [50][51][52] and that intestinal expression of PGC1α is increased under diabetic conditions, 53) our findings indicate that these transcriptional factors may play important roles in the regulation of NPC1L1 expression under diabetic conditions and at least partly account for clinical associations between progressions of T2DM and other cholesterol-related diseases such as dyslipidemia and NAFLD/ NASH. 54,55) …”
Section: Npc1l1 and T2dmsupporting
confidence: 56%
See 1 more Smart Citation
“…Regarding the regulatory mechanism of NPC1L1 expression, we demonstrated that, in addition to SREBP2, several transcriptional factors such as hepatocyte nuclear factor 4α (HNF4α/NR2A1), peroxisome proliferator-activated receptor α (PPARα/NR1C1), and PPARγ coactivator 1α (PGC1α) positively regulate the mRNA expression of NPC1L1. 15,49) Taken together with facts that both HNF4α and PPARα are involved in the pathogenesis of diabetes [50][51][52] and that intestinal expression of PGC1α is increased under diabetic conditions, 53) our findings indicate that these transcriptional factors may play important roles in the regulation of NPC1L1 expression under diabetic conditions and at least partly account for clinical associations between progressions of T2DM and other cholesterol-related diseases such as dyslipidemia and NAFLD/ NASH. 54,55) …”
Section: Npc1l1 and T2dmsupporting
confidence: 56%
“…14,15) Since SREBP2 is activated when intracellular cholesterol level is decreased, NPC1L1 expression increases in response to cholesterol deficiency via the SREBP2-mediated transcription. In addition to the expression level, cellular localization of NPC1L1 protein is also regulated by cholesterol.…”
Section: Npc1l1 and Dyslipidemiamentioning
confidence: 99%
“…It is, however, important to note that the contribution of other pathways beside DNA methylation in dictating the differential expression of intestinal NPC1L1 is also possible. For example, various transcription factors such as SREBP2 and HNF1␣ are known to modulate NPC1L1 expression (7,8). These and other transcription factors may play a role in its distribution along the duodenal-colonic axis.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, NPC1L1 expression has been shown to be modulated at the transcriptional level. For example, SREBP2 and HNF4␣ transcription factors have been shown to stimulate NPC1L1 promoter activity and increase its mRNA expression (7,8). Because the expression of these transcription factors is not intestinal segment-specific (9, 10), their effects on gene transcription may not explain the region-specific expression of intestinal NPC1L1 mRNA.…”
mentioning
confidence: 99%
“…NPC1L1 の転写調節に関しては, sterol responsive element binding protein 2(SREBP2) 13,14) 及び hepatocyte nuclear factor 4a(HNF4a) 14 …”
unclassified